Aurora on Ganymede. Issue 5 (17th May 2013) - McGrath, Melissa A.; Jia, Xianzhe; Retherford, Kurt; Feldman, Paul D.; Strobel, Darrell F.; Saur, Joachim
Abstract : [1] We present four sets of ultraviolet images of Ganymede acquired with the Hubble Space Telescope (HST) from 1998 to 2007, all of which show auroral emission from electron excited atomic oxygen. The three different hemispheres of Ganymede captured in the observations show strikingly different emission morphologies. Ultraviolet emission at 1356 Å is brightest at relatively high latitude on the orbital trailing (upstream plasma) hemisphere and in an auroral oval that extends to as low as 10°N latitude on the orbital leading (downstream plasma) hemisphere. Two sets of images of the Jupiter‐facing hemisphere acquired at nearly the same sub‐Earth longitude but separated by 4 years show very similar emission morphology that is consistent with the pattern of emission seen in the upstream and downstream images: the emission is at high latitude in the upstream quadrant and at low latitude in the downstream quadrant. This implies that the large‐scale, nominal "auroral oval" on Ganymede is apparently quite stable with time, despite significant brightness fluctuations within the overall stable pattern during the 10–30 min time scale between individual images. The overall emission morphology appears to be driven primarily by the strong Jovian magnetospheric plasma interaction with Ganymede and does not appear to be strongly influenced by the orientation of the background Jovian magnetic field. The observed auroral oval pattern is reasonably well matched by a magnetohydrodymanic (MHD) model optimized to fit the Galileo magnetic field measurements near Ganymede. The location of the auroral oval from these data provides a reasonable match to the location of the well‐defined visible boundary of the Ganymede polar cap except in the northern, leading hemisphere. Key Points: New observations of Ganymede auroral emission. Ganymede auroral oval well‐matched by Jia et al. models. Reasonable match between auroral oval location and polar cap boundary.